Synthesis of symmetrical secondary oligoethylene glycolated amines from diethanolamine. Issue 25 (15th June 2022) - Yang, Hao; Li, Yu; Lin, Ruoyun; Ouyang, Zhen; Han, Mingli; Zhu, Lijun; Chen, Shizhen; Zhou, Xin; Jiang, Zhong-Xing
Abstract : A convenient and scalable three-step synthesis of symmetrical M-OEGs secondary amines with structural diversity was developed from commercially available diethanolamine and avoided the use of explosive sodium azide. Abstract : Monodisperse oligoethylene glycols (M-OEGs)-containing symmetrical secondary amines are highly valuable synthetic intermediates in drug development and materials sciences. Scalable three-step synthesis of M-OEGs secondary amines with flexible M-OEGs and/or alkyl chains is described herein. Through reduction amination of diethanolamine, Williamson ether synthesis, and subsequent deprotection, a series of M-OEGs secondary amines with diverse and fine-tunable chemical structures were conveniently prepared. The presented strategy is attractive with readily available starting materials, simple catalytic systems, scalable synthesis, and avoids the use of explosive sodium azide.